A rare congenital tumor: a case report of sacrococcygeal teratoma - Akkuş, Ali Murat; Akpınar, Cem; Türkaslan, Tayfun; Özsoy, Zafer; Özay, Pınar (Cerrahpaşa Medical Journal, 2014)
Teratomas develop most frequently in the sacrococygeum and is an uncommon neoplasm. It most commonly presents in infancy particularly in neonates. Females are affected two times more often than males, but males are more likely to have malignant tumors. Prognosis is related to patients age and to the histologic characteristic of the tumor. Bening teratomas are noninvasive, cystic and contain calcifications. Surgery is the primary treatment although malignant tumors can be treated after the surgery with chemotherapy. In this case report, we present an interesting and misdiagnosed patient.